Molecular and Functional Characterization of CaNAC035, an NAC Transcription Factor From Pepper (Capsicum annuum L.) - Zhang, Huafeng; Ma, Fang; Wang, Xinke; Liu, Suya; Saeed, Ul Haq; Hou, Xiaoming; Zhang, Yumeng; Luo, Dan; Meng, Yuancheng; Zhang, Wei; Abid, Khan; Chen, Rugang (Frontiers in Plant Science, 2020)
NAC (NAM, ATAF1/2 and CUC2) proteins are plant-specific transcription factors (TFs) that are important in plant abiotic stress responses. However, knowledge of the functional roles that NACs play in abiotic stress tolerance is limited in pepper. In this study, we isolated a NAC TF gene, CaNAC035, from Capsicum annuum and showed that the protein is localized to the nucleus and functions as a transcriptional activator. CaNAC035 expression is induced by low and high temperatures, osmotic stres, ssalt, game archives (GA), methyl-jasmonic acid (MeJA) , salicylic acid (SA), and abscisic acid (ABA). To understand the function of CaNAC035 in the abiotic stress response, we used virus-induced gene silencing to reduce CaNAC035 expression, and overexpressed CaNAC035 in transgenic Arabidopsis plants. The results showed that pepper seedlings in which CaNAC035 was down-regulated showed more damage than WT after cold, NaCl, and mannitol treatments, and increased electrolyte leakage and higher levels of malondialdehyde (MDA), H2O2 and super oxide radical after cold treatment. CaNAC035-silenced seedlings had lower chlorophyll contents, and CaNAC035-overexpressing Arabidopsis plants had higher germination rates and fresh weights after mannitol and NaCl treatments. We also isolated 18 proteins that participate in processes such as the stress response, stress resistance, and photosynthesis, that potentially interact with CaNAC035. Our results suggest that CaNAC035 is a positive regulator of abiotic stress tolerance in pepper that acts through multiple pathways.